La Navidad de Winnie Puh - Talkington, Bruce; Moore, Sparky; Ware, Gene; Santacruz, Daniel; Walt Disney Productions; Alvin S. White Studio (New York : Disney Press, 1994)
Winnie discovers the importance of stockings in the celebration of Christmas and the tradition of giving and receiving.
Translation of: Disney's Winnie the Pooh's Christmas.
Keywords: Christmas -- Fiction; Christmas fiction